Hypoglycemic effect of Satureja montanum L. hydroethanolic extract on diabetic rats - Mirazi Naser; Rezaei Maryam; Mirhoseini Mahmoud (Shahrekord University of Medical Sciences, 2016)
ntroduction: Diabetes is one of the most prevalent metabolic disorders which is associated withseveral complications in different organs. Nowadays, medicinal herbs are being widely used totreat diseases. This study was conducted to study the hypoglycemic effect of Satureja montanum in diabetic male rats.Methods: In this study 42 male Wistar rats were randomly assigned to 7 equal groups includingcontrol, diabetic control, treatments 1, 2, and 3, metformin-treated diabetic, and healthytreated with Satureja montanum. To induce diabetes streptozotocin (STZ) at 60 mg/kg wasintraperitoneally (ip) administered. The animals were treated daily with Satureja montanumextract (ip) for one week and their blood glucose was measured daily.Results: Satureja montanum extract could significantly decrease blood glucose. The greatest effectof the extract was seen on day 8 at 800 mg/kg (P < 0.001). Satureja montanum extract caused asignificant increase in serum insulin compared to the control group (P < 0. 001).Conclusion: The findings of this study indicate that Satureja montanum hydroethanolic extractis able to significantly decrease blood glucose of diabetic rats possibly with a stimulatory effect onbeta cells.